A New Instrument and Method for Nitrogen-loss Studies in Oxygen Deficient Zones - Reed, Andrew (My University, 2018)
The ocean’s biogeochemical cycles are coming under increasing stress due to global climate change and anthropogenic emissions of carbon dioxide. Three different factors are stressing the oceans: rising temperatures, acidification, and deoxygenation [Gruber 2011]. Rising temperatures are predicted to increase stratification and slow-down global ocean circulation. We examine the change in the rates of formation and characteristics of Antarctic Bottom Water (AABW) in the Australia-Antarctic Basin from repeat hydrographic sections. Using changes in CFC-11 and CFC-12 concentrations, we find that AABW formation rates corrected for seasonality decrease by approximately 20%, from 0.38 ± 0.04 m2 s−1 in 1991 to 0.30 ± 0.02 m2 s−1 in 2008. Additionally, we find the sampled AABW warmed and increased in salinity, likely due to the increasing influence of bottom water formed in the Ross Sea over fresh, cold waters formed offshore of Adelie Land. Oceanic deoxygenation has the potential to significantly alter the global nitrogen cycle due to potential expansion of Oxygen Deficient Zones (ODZs), which are regions of the pelagic ocean where oxygen concentrations are nearly or functionally zero. In ODZs, microbes utilize biologically-available fixed nitrogen to either respire organic matter (denitrification) or fix new organic matter (anammox), converting the fixed nitrogen into N2-gas. An alternative method to the traditional method of measuring dissolved N2-gas by N2:Ar mass spectrometry is using in-situ measurements of total dissolved gas pressure (gas tension) using a gas tension device (GTD). We designed and characterized a new GTD which uses a custom designed small diameter (4 cm) thin (130 µm) incompressible composite Teflon-AF 2400 membrane. The new GTD eliminates issues of hydrostatic pressure-generated transients, changes to response times, and reverse osmosis, which plagued existing versions of GTDs using a compressible polydimethylsiloxane (PDMS) membrane. We demonstrate that two of the new GTDs, attached to different gas-sensing floats, measure the in-situ gas tension of the Eastern Tropical North Pacific (ETNP) ODZ with accuracies of 0.6% and 0.4% compared to gas-tension calculated from independent measurements of N2:Ar by mass spectrometry and O2 by Winkler titration. Next, we present a new method for calculating the biogenic-N2 from gas tension. N2 is derived by subtracting the O2, Ar, climatological CO2, and water vapor pressure from the gas tension. Argon is estimated by developing a linear-mixing-model based on T-S analysis to interpolate an independent argon concentration data set in the ODZ to our observations. This model is also applied to estimate the abiotic-N2 concentrations to account for supersaturations due to mixing and warming. Peak biogenic-N2 concentrations are 11.33 ± 1.75 µM/kg (F77) and 6.40 ± 2.07 µM/kg (F78), along with an independent estimate of 6.55 ± 2.05 µM/kg N2 calculated from concurrently-sampled N2:Ar ratios and 5.26 ± 1.22 µM/kg from nutrients along the σθ = 26.2 kg/m-3 isopycnal, which corresponds with the core volume of the ODZ. Lastly, we present a high-precision determination of the hydrostatic-pressure effect on the partial pressures of nitrogen, oxygen, and argon dissolved in freshwater by direct measurement with a GTD and an oxygen optode. Thermodynamics predict that partial pressure increases of 14% 1000 dbar-1 for N2 and O2 with molar volumes of 31 ± 2 mL/mol N2 and 32 ± 2 mL/mol. Hydrostatic pressures ranged from 0 to 550 dbar, pressures typical in the intermediate to upper ocean. Our experiment directly measures the change in partial pressures for a commensurate change in hydrostatic pressure. We found a change of 12.99 ± 0.14% 1000 dbar-1 for O2 and 15.53 ± 0.12% 1000 dbar-1 for N2 with calculated molar volumes of 29.87 ± 0.35 mL/mol for O2 and 35.12 ± 0.27 mL/mol for N2. The results of our work is a new instrument and method which can be used for long-term autonomous biogeochemical monitoring of changes in the temporal and spatial variability of nitrogen-loss in ODZs.
Thesis (Ph.D.)--University of Washington, 2018
Keywords: Denitrification; Dissolved gases; Gas Tension Device; Henry's Law; Nitrogen; Oxygen Minimum Zones; Chemical oceanography; Physical oceanography; Ocean engineering; Oceanography